2015
DOI: 10.1007/s10753-015-0196-z
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Incorporation of Non-Methylene-Interrupted Fatty Acids (NMIFA) in Murine Microglial BV-2 Cells Reduces Pro-Inflammatory Mediator Production

Abstract: Sciadonic acid (SCA), pinolenic acid (PNA), and Δ7-eicosatrienoic acid (Δ7-ETrA) are three non-methylene-interrupted fatty acids (NMIFA). Using murine microglial BV-2 cells, this study determined how NMIFA incorporation modulated phospholipid fatty acid composition and the production of pro-inflammatory mediators. Each NMIFA was rapidly taken up and incorporated in BV-2 cells, resulting in the differential redistribution of total lipids. The cellular phospholipid fatty acid compositions were altered, and a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(75 citation statements)
references
References 29 publications
3
72
0
Order By: Relevance
“…Pine nut oil is extracted from pine nut ( Pinus pinea ) and has been widely used for inflammation, appetite, body weight, blood lipids, insulin sensitivity, cancer metastasis, liver steatosis and hyperinsulinemia . Pine nut oil can be extracted by cold pressing, solvent extraction and supercritical CO 2 extraction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pine nut oil is extracted from pine nut ( Pinus pinea ) and has been widely used for inflammation, appetite, body weight, blood lipids, insulin sensitivity, cancer metastasis, liver steatosis and hyperinsulinemia . Pine nut oil can be extracted by cold pressing, solvent extraction and supercritical CO 2 extraction.…”
Section: Introductionmentioning
confidence: 99%
“…3 Pine nut oil is extracted from pine nut (Pinus pinea) and has been widely used for inflammation, appetite, body weight, blood lipids, insulin sensitivity, cancer metastasis, liver steatosis and hyperinsulinemia. [4][5][6][7][8][9] Pine nut oil can be extracted by cold pressing, solvent extraction and supercritical CO 2 extraction. Several types of fatty acids exist in pine nut oil, comprising 50% polyunsaturated fatty acids, 40% monounsaturated fatty acids and 10% saturated fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…Another line of approach could also imply oxidized derivatives of FA. Scia was described as a modulator of inflammation as it reduced the production of PGE 2 from macrophages, infected epithelial cells or microglial BV-2 cells in vitro 10,11,13 . The present study did not strengthen this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Pteropods range from a few mm to a few cm size, so their ingestion by GSM, if it occurs, would be surprising. The biological role and function of NMI-FAs are not well understood, and whilst it has been suggested that their function is analogous to the n-3 LC-PUFAs, EPA and DHA (Tanaka et al, 1999), NMI-FAs may have further unique biological properties particularly in influencing inflammation (Chen, Chuang, Liao, Huang, & Lin, 2015). The NMI-FAs in GSM were highest over the late autumn-winter months (May-August; 4 g/100 g of FA), but were maintained at reduced levels over the spring-summer seasons (2.0-2.5 g/100 g of FA) (see Table 2).…”
Section: Seasonal Changes In Gsmmentioning
confidence: 99%
“…The NMI-FAs in GSM were highest over the late autumn-winter months (May-August; 4 g/100 g of FA), but were maintained at reduced levels over the spring-summer seasons (2.0-2.5 g/100 g of FA) (see Table 2). The biological role and function of NMI-FAs are not well understood, and whilst it has been suggested that their function is analogous to the n-3 LC-PUFAs, EPA and DHA (Tanaka et al, 1999), NMI-FAs may have further unique biological properties particularly in influencing inflammation (Chen, Chuang, Liao, Huang, & Lin, 2015).…”
Section: Seasonal Changes In Gsmmentioning
confidence: 99%